Development of an analytical approach for identification and quantification of 5-alpha-androst-16-en-3-one in human milk - Hartmann, Constanze; Mayenzet, Fabienne; Larcinese, Jean-Paul; Haefliger, Olivier P.; Büttner, Andrea; Starkenmann, Christian (Steroids, 2013)
A method was developed for the quantification of 5-alpha-androst-16-en-3-one in human breast milk based on application of a stable isotope dilution assay using 5 alpha-androst-16-en-3-one-6, 6-d(2). The procedure includes extraction of the human milk by hexane with subsequent clean-up of the obtained extract by gel permeation and silica gel column chromatography. The extracted samples were analyzed by gas chromatography-mass spectrometry. Using this method 5-alpha-androst-16-en-3-one could be identified and for the first time quantified in a concentration range of 26-155 ng/kg in human milk. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Gel permeation chromatography; GC-MS; 5-alpha-Androst-16-en-3-one; Breast milk; Stable isotope dilution assay